Poverty Elimination and Upliftment of Living Standard Through Microfinance (A Case Study of Selected Districts of Uttar Pradesh) - Agarwal, Himanshu; Ahmed, Sarfraj (Journal of Commerce and Trade, 2021)
The development process in India is not yielding the desired results such as standard of living, extended per capita income and basic welfare facilities to all. The main culprit is low capital formation capacity of the citizens. Therefore, broader poverty line, low standard of living and weak per capita income is persisting for years. Effective allocation of regular credit, quick small loans and financial inclusion are needed strongly. Microfinance is bringing in a demographic change from lower to middle class with the support of institutional credit. Emergency loans, consumption loans, business loans, working capital loans, housing loans, micro-pensions, micro-insurance, direct benefit transfers, support amount to female account holders and other such financial services are benefiting low-income groups. Present study is based upon primary as well as secondary data. The area is Meerut, Bulandshahr and Muzaffarnangar districts of Uttar Pradesh. The study is a descriptive study. The microfinance sector is undergoing a drastic change with the advents of rising competition in consumer durables, increasing awareness about standards of living, advances in technology and evolving regulatory platforms. AI, digitalization, app-based transactions have converted microfinance in a wide-horizon business model. Financial security, data safety, transparency of transactions, fair transfer of GST and accounted information of transactions. The microfinance programme not only establishes economic, social and political empowerment of its members, but also its overall identity.